Crystal Oscillator Design and Temperature Compensation - Frerking, Marvin. author. aut Link
XVI, 240 p.
Keywords: Crystal oscillators have been in use now for well over SO years-one of the first was built by W. G. Cady in 1921. Today, millions of them are made every year, covering a range of frequencies from a few Kilohertz to several hundred Mega hertz and a range of stabilities from a fraction of one percent to a few parts in ten to the thirteenth, with most of them, by far, still in the range of several tens of parts per million.Their major application has long been the stabilization of fre quencies in transmitters and receivers, and indeed, the utilization of the frequency spectrum would be in utter chaos, and the communication systems as we know them today unthinkable,'without crystal oscillators. With the need to accommodate ever increasing numbers of users in a limited spectrum space, this traditional application will continue to grow for the fore seeable future, and ever tighter tolerances will have to be met by an ever larger percentage of these devices.